Narrative techno-enhancement: the impact of the digital visual effects (DVFx) in creative narrative performance - Hasrul Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Globalization of technology primarily in the field of film, media and communication studies has also impacted the creativity in visual presentation and storytelling. The occurrence of technological changes that involve creative work will undoubtedly lead to a new assessment of creativity. Hence, technology and creativity are likely to represent a new creative possibility and measurement in the field of film production. Digital Visual Effects (DVFx) provides new kind of creativity based on technology to the creative visual presentation and creative narrative enhancement. We have learned that story and narratives are the priorities that need to be secure in a movie; however, the spectacular element produced by using DVFx show the progress and development of technology used in the film production process, especially to the creative narrative. Hence the question that needs to address is; how these elements of technology integrated with the story and narrative filmmaking? Generally, this article will focus on the role and impact of DVFx as narrative techno-enhancement in the storytelling, and narrative presentation compared the technical visual presentation aspect. Precisely, this article analyses the impact on DVFx among professionals in Malaysia, India, and Australia’s film industries to enhance creative narrative performance. Narrative interstate relies on our understanding of the use of technology to create and convey stories. Presentation of stories also means communicating and transferring the meaning to the audiences. In addition to functioning as narrative techno-enhancement, DVFx opens the exploration of value in creative storytelling such as digital narrative and digital interactive storytelling for the audience in the 21st century.